Glioblastoma multiforme: A rare case of GBM - Albert Paul Varghese; Anurag Luharia; Ashish Uke; Monika Luharia; Gaurav Mishra; Sneha Shrungare; Neha Rahul (Journal of Krishna Institute of Medical Sciences University)
The most rapid and severe primary brain tumor in adults is Glioblastoma Multiforme (GBM), which is known for its rapid development and high invasiveness. GBM is still associated with a dismal prognosis, even with advancements in multiple treatment modalities like chemotherapy, radiotherapy, and surgical resection. The typical survival following diagnosis is only 12 to 15 months. GBM is incredibly heterogeneous due to its complicated genetic and molecular causes, which makes effective therapy very challenging. Three key molecular pathways associated with the pathophysiology of GBM include PI3K/AKT/mTOR, Rb signaling, and the p53 tumor suppressor. There are promising prospects to improve clinical outcomes with new treatment techniques that target these pathways in addition to innovative strategies like immunotherapy and personalized medicine. This research investigates characteristic approaches to GBM management which includes post op adjuvant radiotherapy with concurrent temozolomide followed by adjuvant chemotherapy for 6 to 12 cycles.